LB1529. Randomized, Controlled Phase 3 Study of anti-C5a Vilobelimab's Effect on Mortality in Critically Ill COVID-19 Patients: A Therapy for Viral Pneumonia. (15th December 2022) - Mourvillier, Bruno; Vlaar, Alexander; Witzenrath, Martin; Bauer, Michael; Heunks, Leo; Vasquez, Luis Hercilla; Welte, Tobias; van Paassen, Pieter; De Bruin, Sanne; Lim, Endry H T; Tuinman, Pieter R; Saraiva, Jose F; et al.
Abstract: Background: SARS-CoV-2 induces endothelial damage and activates the complement system. In severe COVID-19 patients, complement split factor C5a is highly elevated leading to inflammation that contributes to multiorgan failure. The anti-C5a monoclonal antibody, Vilobelimab (Vilo), which preserves the membrane attack complex (MAC), was investigated in an adaptively designed, randomized double-blind, placebo (P)-controlled Phase 3 international multicenter study for survival in critically ill COVID-19 patients (pts). Methods: COVID-19 pneumonia pts (N=368; Vilo n=177, P n=191), mechanically ventilated within 48 hrs before treatment, received up to 6, 800 mg infusions of Vilo or P on top of standard of care. The primary and main secondary endpoints were 28-day (d) and 60-d all-cause mortality. Results: Pts enrolled in the study were on corticosteroids (97%) and anti-coagulants (98%) as standard of care. A smaller proportion (20%) were either continuing or had taken immunomodulators such as tocilizumab and baricitinib prior to receiving Vilo. The 28-d all-cause mortality was 31.7% with Vilo vs 41.6% with P (Kaplan-Meier estimates; Cox regression site-stratified, HR 0.73; 95% CI:0.50-1.06; P=0.094), representing a 23.8% relative mortality reduction. In predefined primary outcome analysis without site stratification, however, Vilo significantly reduced mortality at 28 (HR 0.67; 95% CI:0.48-0.96; P=0.027) and 60 days (HR 0.67; 95% CI:0.48-0.92; P=0.016). Vilo also significantly reduced 28-d mortality in more severe pts with baseline WHO ordinal scale score of 7 (n=237, HR 0.62; 95% CI:0.40-0.95; P=0.028), severe ARDS/PaO2 /FiO2 ≤ 100 mmHg (n=98, HR 0.55; 95% CI:0.30-0.98; P=0.044) and eGFR < 60 mL/min/1.73m 2 (n=108, HR 0.55; 95% CI:0.31-0.96; P=0.036). Treatment-emergent AEs were 90.9% Vilo vs 91.0% P. Infections were comparable: Vilo 62.9%, P 59.3%. Infection incidence per 100 Pt days were equal. No meningococcal infections were reported. Serious AEs were 58.9% Vilo, 63.5% P. Conclusion: Vilo significantly reduced mortality at 28 and 60 days in critically ill COVID-19 pts with no increase in infections suggesting the importance of targeting C5a while preserving MAC. Vilo targets inflammation which may represent an approach to treat sepsis and ARDS caused by other respiratory viruses. Disclosures: Alexander Vlaar, MD, PhD, InflaRx GmbH: Advisor/Consultant Maria Habel, PhD, InflaRx GmbH: Stocks/Bonds Claus Thielert, PhD, InflaRx GmbH: Stocks/Bonds James Dickinson, MSc, InflaRx GmbH: Stocks/Bonds simon Rückinger, PhD, InflaRx GmbH: Advisor/Consultant Robert Zerbib, MSc, InflaRx GmbH: Stocks/Bonds Dorothee Neukirchen, PhD, InflaRx GmbH: Stocks/Bonds Korinna Pilz, MD, MSc, InflaRx GmbH: Ownership Interest|InflaRx GmbH: Stocks/Bonds Renfeng Guo, MD, InflaRx GmbH: Board Member|InflaRx GmbH: CSO|InflaRx GmbH: Ownership Interest|InflaRx GmbH: Stocks/Bonds Diederik van de Beek, MD, PhD, InflaRx GmbH: Advisor/Consultant Niels Riedemann, MD, PhD, InflaRx GmbH: Board Member|InflaRx GmbH: CEO|InflaRx GmbH: Ownership Interest|InflaRx GmbH: Stocks/Bonds.